“Go West Young Joan!” Mark Twain’s Personal Recollections of Joan of Arc (1896) - Jennifer Kilgore-Caradec (Perspectives Médiévales)
The artifices that Mark Twain used to publish his novel Personal Recollections of Joan of Arc by Sieur Louis de Conte in 1895-6 mystified his readers no less than the appeal of the heroine for an avowed atheist. Twain’s earliest encounter with Joan, when he was 15 years old, while working as a printer, would influence his decision to become a writer, but it was only near the end of his life that she was to become a visible preoccupation. During the Dreyfus Affair Twain and Charles Péguy were both composing literary works about Joan of Arc that reflected their own political and social commitments. In Twain’s case, later writings and speeches about Joan clarify his interest as well as a pro-American bias (Louis de Conte narrates in 1492!) that did not hesitate to also critique American policies.